0349 Medical Encounters for Sleep Disorders among Mixed Age Male and Female Active Duty US Air Force between 2016 and 2017. (12th April 2019) - Duncan, Joshua R; Schroeder, Paul J; Williams, Jennifer
Abstract: Introduction: Sleep disorders are prevalent among military service members. Poor sleep not only impairs mental and physical health, but is costly to treat. Although it has been shown that, among military samples, demographic variables are associated with greater risk for some sleep disorders, additional research is needed to understand the relationship. In the present study we examined the age and gender of Airmen seeking treatment for five sleep disorders that received the highest frequencies of medical encounters between fiscal years (FY) 2016 and 2017. Methods: Data on medical encounters and demographics for active duty Airmen between FY 2016 and 2017 were obtained from the Military Health System MHS Mart (M2) database. Results: Among 34 sleep-associated disorders identified in the dataset, the five disorders that received the most medical encounters for FY's 2016 and 2017 were: insomnia-unspecified (58.65% of encounters), primary insomnia (15.16%), sleep disorder-unspecified (3.53%), other insomnia (3.46%), and inadequate sleep hygiene (3.36%). Across the five disorders the percentages of medical encounters were significantly lower for 2017 (45.36%) as compared with 2016 (54.64%) (p < .01), greater for male Airmen (70.43%) than females (29.57%) (p < .01), and significantly greater for Airmen ages 25-34 years (39.97%) than those aged 18-24 (24.11%), 35-44 (29.64%), and 45-64 years (6.28%) (p's < .01). Examination of within-disorders encounter rates revealed statistically similar percentages of encounters among inadequate sleep hygiene and other insomnia for 2016 and 2017 and for Airmen in the 18-24 and 35-44 age groups (p's > .05). Similar percentages of encounters were observed among inadequate sleep hygiene, other insomnia, and sleep disorder-unspecified and for the 18-24 and 25-34 year age groups (p's > .05). All other comparisons were statistically significantly different (p's < .05). Conclusion: Despite declines in medical encounters, sleep issues persist among active duty Airmen, especially among middle-age males. Raising awareness of both the symptoms of sleep disorders and treatment options could reduce future medical encounters and improve overall health and readiness. Support (If Any): None.